The politics of accountability: violence, mass punishment and restorative justice - Rasmussen, Cameron W. (Contemporary justice review, 2023)
Fifty years of rising incarceration and mass punishment have solidified the carceral state as central to US governance and culture, and entrenched the perception of punishment as the most effective and moral response to interpersonal violence. Today, within a growing discourse challenging punishment as the primary response to interpersonal violence, restorative justice (RJ) is the most commonly promoted alternative. Yet in the context of the criminal legal system and in the broader RJ ecosystem, RJ responses to violence are limited, receiving minimal public and academic attention. This paper traces the developments of mass punishment and RJ over the last 50 years, analyzing their contrasting political and social evolutions. This analysis illustrates how punishment has captured the political, legal and social possibilities as it relates to violence, and how and why the field of RJ has been limited in its ability to advance non-punitive accountability-based approaches to violence. In addition, lessons are drawn from these instructive histories for the growing RJ efforts to address violence, to consider and challenge the varying forces that have made growing these responses difficult.